De oratie van M.D. Ozinga (1948), het ontstaan van de gotiek en het probleem van stijlperioden (Bulletin KNOB, 1996)
In 1947 M.D. Ozinga was appointed at an art-historical institute of the university as the first professor of the history of architecture in The Netherlands. During his first years as a professor his previous work at the Dutch Historic Buildings and Monuments Commission provided him with material for research into the architecture of the Middle Ages. In the inaugural lecture delivered when he officially accepted the professorship in 1948, he tried to find the causes of changes in Medieval architecture, notably the rise of the Gothic style.In foreign literature possible explanations had been suggested, but these could hardly satisfy him. Ozinga performed his research within the framework of the successive style periods, a classification model which has been criticized ever since, but has never been revised. He disagreed with Panofsky, who attributed a rather large role in the rise of the Gothic style to abbot Suger of Saint-Denis. Ozinga himself opted for a combination of various factors, all of them having contributed to the rise of the Gothic style, with a leading part played by the artist. The fact that in the Middle Ages there was no such thing as a conception of style yet did not induce Ozinga to come up with an essentially different outlook on this matter.